2021
DOI: 10.2147/ndt.s289357
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Aβ42 to Total Cerebral Small Vessel Disease Score Improves the Prediction for Cognitive Impairment in Cerebral Small Vessel Disease Patients

Abstract: Purpose: To investigate the associations between concentrations of Aβ 40 and Aβ 42 and vascular cognitive impairment (VCI) in cerebral small vessel disease (CSVD) patients and evaluate the value of combination of levels of Aβ 40 or Aβ 42 and the total CSVD score in predicting VCI. Patients and Methods: A total of 199 CSVD patients were divided into VCI group and non-VCI group according to the criteria of VCI. Demographic data, MRI markers of CSVD, blood pressure, vascular risk factors, laboratory markers, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 42 publications
(54 reference statements)
1
5
0
Order By: Relevance
“…Whereas previous studies only considered the interaction of individual SVD markers alone with Aβ, our study extended the results to global SVD burden, confirming that global SVD*Aβ can predict executive, memory and language decline in MCI subjects. This was in line with a previous study indicating that the combination of Aβ and global SVD burdens could meaningfully predict cognitive impairment (Liu et al, 2021). Nevertheless, that study only conducted a cross‐sectional analysis, while our study included a 4‐year longitudinal analysis, affirming the predictive value of it, and further revealed how these associations changed over time.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Whereas previous studies only considered the interaction of individual SVD markers alone with Aβ, our study extended the results to global SVD burden, confirming that global SVD*Aβ can predict executive, memory and language decline in MCI subjects. This was in line with a previous study indicating that the combination of Aβ and global SVD burdens could meaningfully predict cognitive impairment (Liu et al, 2021). Nevertheless, that study only conducted a cross‐sectional analysis, while our study included a 4‐year longitudinal analysis, affirming the predictive value of it, and further revealed how these associations changed over time.…”
Section: Discussionsupporting
confidence: 93%
“…This may explain how SVD and AD pathology interact. A recent study showed that the interaction of Aβ and WMH can affect cognitive function (Saridin et al, 2020), while some other studies (Banerjee et al, 2017;Freeze et al, 2017) (Liu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides vascular Aβ lesions found in CAA, an association between Aβ and CSVD has been reported in many studies. Liu et al found that serum Aβ42 combined with the CSVD score could predict cognitive impairment in patients with CSVD (Liu et al, 2021 ). An 8-year longitudinal study suggested that Aβ positivity in amyloid PET was an independent predictor of functional disability regardless of the occurrence of stroke in patients with subcortical VCI (Kang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Common risk factors, such as coagulation abnormalities, impaired vascular EC function, inflammatory reactions, and uremia-related factors, may occur in patients with ischemic stroke and CSVD, and it has an undesirable effect ( 72 ). Furthermore, latest research shows that Aβ-42 combined with the CSVD score can also be used to predict vascular cognitive dysfunction (VCI) in patients with CSVD ( 73 ).…”
Section: Biochemical Markers and Influencing Factorsmentioning
confidence: 99%